How Do Switching Boredom, Commitment Mix, and Attractiveness Influence Cinema Viewers’ Intentions to Switch in Indonesian Theaters? Attractiveness On Switching Intention - Helmi, Tengku Ahmad; Pane, Sri Gustina; Patiro, Shine Pintor Siolemba; Yusriani, Sri (Journal of Islamic Economics and Business, 2026)
This paper examines the determinants of cinema viewers’ switching intention in Indonesia, with a focus on switching boredom, service commitment mix, and switching attractiveness. The study is motivated by the increasing competition in the entertainment industry, where audience preferences are dynamic and switching behavior is common. The central problem addressed is why cinema customers decide to switch despite existing commitments, raising the research question: How do switching boredom, service commitment mix, and switching attractiveness influence cinema viewers’ switching intentions in Indonesian theaters? Unlike previous studies that treat commitment as a switching barrier, this paper reveals that service commitment may not prevent switching when its affective, cognitive, normative, and conative components fail to engage customers. This nuance highlights a gap in the literature on customer behavior in the entertainment sector. The study employs a quantitative approach using structured online questionnaires distributed to 200 cinema-goers, selected through purposive non-probability sampling. The data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that switching boredom, service commitment mix, and switching attractiveness significantly and positively affect switching intention. Moreover, boredom and attractiveness have a reinforcing linear relationship that intensifies switching behavior. The findings suggest that cinema operators need to mitigate customer boredom and enhance perceived value through innovation and personalized engagement. The study contributes to the understanding of switching behavior in experience-driven services and offers practical implications for sustaining audience loyalty in competitive markets.